Is Left-Sided Infective Endocarditis Prone to Have Embolic Events? - Yoga Yuniadi (The Indonesian Heart Association, 2012)
Infective endocarditis (IE) is an endovascular microbial infection of intracardiac structures facing the blood including of large intrathoracic vessels and of intracardiac foreign bodies. Diagnostic and therapeutic improvement have been recently achieved, however it is still associated with high mortality and embolic events.A lot of studies have been done in search of high risk IE patient, mainly focus on echocardiographic findings. Unfortunatelly, those studies give rise conflicting results. In multicenter prospective European study, 384 consecutive patient with definite IE according to Duke criteria were followed up to 1 year. Using transesophageal echocardiography (TEE), they found that vegetation length is a strong predictor of new embolic event and mortality. In multivariate analysis, vegetation length of > 15 mm has an adjusted relative risk of 1.8 95%CI 1.1 to 2.82, p = 0.02. Combining clinical, microbiological and echocardiography finding may identify high risk patient who will need aggressive therapy.Stuby by Fahmi et al enrolled only limited number of definite IE patients and found that involvement of mitral valve, examined by transthoracal echocardiography (TTE), is a predictor of embolic events. As an initial study in this field among Indonesian subjects, we can compromize with the power of this study to conclude that left side valves involvement is a predictor of embolic event in IE patients. The conclusion it self is make sense in regard to the disease’s pathophysiology.